2018
DOI: 10.2147/dddt.s184053
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of rosuvastatin into breast milk: liquid chromatography–mass spectrometry methodology and clinical recommendations

Abstract: IntroductionRosuvastatin reduces concentrations of total cholesterol (TC) and is used for the management of hypercholesterolemia and prevention of acute coronary syndromes. There are no published reports estimating infant exposure to rosuvastatin through breast milk.PurposeThe aims of this study were to quantify concentrations of rosuvastatin in human milk and plasma from a lactating woman taking rosuvastatin and to investigate potential infant exposure.Materials and methodsA 38-year-old breastfeeding mother w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…There are few studies on breastfeeding and statins in humans. Two studies showed that rosuvastatin is transferred into breast milk, but that statin exposure for the infant seems to be low [27,28]. Others have suggested that the health benefits of breastfeeding while using rosuvastatin may outweigh the low risk of statin exposure for the child [29].…”
Section: Statin Use During Breastfeeding Is Understudiedmentioning
confidence: 99%
“…There are few studies on breastfeeding and statins in humans. Two studies showed that rosuvastatin is transferred into breast milk, but that statin exposure for the infant seems to be low [27,28]. Others have suggested that the health benefits of breastfeeding while using rosuvastatin may outweigh the low risk of statin exposure for the child [29].…”
Section: Statin Use During Breastfeeding Is Understudiedmentioning
confidence: 99%
“…The effects of scutellarin on the rosuvastatin uptake in OATP1B1 transfected HEK293T cells were assayed by LC-MS/MS. The method was validated by examining the selectivity, sensitivity, accuracy, precision, recovery, matrix effect and stability profiles of rosuvastatin 16 .…”
Section: Determination Of Rosuvastatin Uptake In Oatp1b1-hek293t Cellmentioning
confidence: 99%
“…The methods for the collection and analysis of human milk and plasma samples were consistent with those described in our previous research (Leggett et al, 2020; Lwin, Gerber, et al, 2018; Lwin, Leggett, et al, 2018). During the study period, the participant took modafinil 300 mg at 9 a.m. and 100 mg at 12:30 p.m. on Day 1, and 300 mg at 9:30 a.m. and 100 mg at 1 p.m. on Day 2.…”
Section: Managementmentioning
confidence: 82%